Cerebral embolization associated with parenchymal seeding of the left atrial myxoma: Potential role of interleukin‐6 and matrix metalloproteinases. Issue 1 (9th August 2020) - Aguilar, Cristian; Carbajal, Tomas; Beltran, Brady E.; Segura, Pedro; Muhammad, Sajjad; Choque‐Velasquez, Joham
Abstract : Systemic embolization has been reported in up to 40% of patients with left atrial myxoma, half of them with cerebral involvement. However, development of intracerebral embolization associated with parenchymal seeding of the myxoma emboli is an extremely rare complication, with only 36 histologically diagnosed cases reported in the published literature. We describe a 69‐year‐old woman who arrived at the emergency service with hemiparesis associated with drug‐resistant epilepsy and a medical history of resection of a left atrial myxoma 10 months previously. Cranial computed tomography revealed multiple large lesions of heterogeneous density and cystic components in the occipital lobes and posterior fossa parenchyma. Histopathological analyses after stereotactic biopsy of the occipital lesion revealed infiltrative myxoma cells with benign histological findings and uniform expression of calretinin similar to that of the primary cardiac myxoma. Additional immunohistochemical studies confirmed brain parenchymal seeding of the myxoma cells with strong expression of interleukin‐6 (IL‐6) and focal expression of matrix metalloproteinases‐2 (MMP‐2). Here, we discuss the clinicopathological features of intracerebral embolization of left atrial myxomas associated with progressive parenchymal seeding of the tumor emboli and the potential pathogenic role of IL‐6 and MMPs.